Developing A Student Handout of English Material for Grade Eight - Nadia Tassya Pratiwi; Dewi Nopita; Rona Elfiza (Juliet, 2022)
This study aimed to develop a student handout as an English material for eighth grade and to know the validity and practicality of it. A handout was one form of teaching material that could be used and could support the learning process. This study was a research and development. The model of research and development used was the 4D development model proposed by Thiagarajan which has been modified into 3D by Wati (2012). 3D model only consists of three main steps, that are Define, Design, and Development. The results of the study showed that the student handout has been developed by following the steps of the development model which was used. Through validation by two material expert validators, the validity result of the initial design of student handout has obtained the average score percentage from validator 1 was 84.72% with very valid category and from validator 2 was 75% with valid category. In a limited trial, the practicality result of the student handout reached to average score percentage of students’ responses was 82.24% with very practical category, so that the final product of student handout is obtained.